Meningkatkan Kepercayaan Diri Pada Anak Melalui Platform Youtobe - Dinda Ayu Lestari; Erni Asbi Asneli (Yayasan Literasi Sains Indonesia, 2022)
Self-confidence is one of the most important aspects of a person's personality. Self-confidence is a very valuable attribute in a person in social life, without self-confidence it will cause many problems in a person. This is because with self-confidence, a person is able to actualize all his potential. Self-confidence is needed by both a child and a parent, individually or in groups. Individuals who are confident will view weaknesses as natural for every individual, because individuals who are confident will turn their weaknesses into motivation to develop their strengths and will not allow their weaknesses to become obstacles in actualizing their strengths.Children who are confident will be able to accept themselves, ready to accept challenges in the sense of wanting to try something new even though they are aware that the possibilities that a person has must and tend to be more successful in doing what he wants. Meanwhile, children who lack self-confidence will be pessimistic in facing challenges, afraid and hesitant to express ideas, indecisive in choosing and often compare themselves with others. Because personality development, mental and intellectual attitudes are formed from an early age and need a process, children's self-confidence needs to be built from an early age.